C how to program with an introduction to C++ Paul Deitel, Harvey Deitel - Deitel, Paul; Deitel, Harvey (Always learning, 2016)
C How to Program is a comprehensive introduction to programming in C. Like other texts of the Deitels' How to Program series, the book serves as a detailed beginner source of information for college students looking to embark on a career in coding, or instructors and software-development professionals seeking to learn how to program with C.